The Role of Innovation and Creativity in Business Management to Enhance SME Economy in the Creative Industry - Ratna; Purnomo, Yudiyanto Joko; Sutrisno (Lembaga Intelektual Muda (LIM) Maluku, 2024)
SMEs are the backbone of Indonesia's economy, contributing significantly to employment and the Gross Domestic Product. The creative industry holds immense potential in driving economic growth, especially in the digital era. This research aims to analyze the role of innovation and creativity in business management to enhance SME economy in the creative industry. The research method employed is a literature review using a qualitative approach. Data were gathered from articles published on Google Scholar between 2013 and 2024. The study findings indicate that the creative industry has become one of Indonesia's most dynamic and rapidly growing economic sectors, with Micro, Small, and Medium Enterprises (MSMEs) playing a vital role as engines of local economic growth, innovation sources, and creativity. Innovation and creativity are key to maintaining competitiveness, developing new products and services, and reaching broader markets. Through innovation, SMEs can develop unique and compelling products, enhance operational efficiency through technology adoption, and optimize marketing strategies and branding. Creativity in product design and customer experience is crucial for attracting consumer interest and distinguishing oneself from competitors